2021
DOI: 10.1128/mbio.02756-21
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Lambda Intranasal Protection and Differential Sex Pathology in a Murine Model of SARS-CoV-2 Infection

Abstract: The COVID-19 pandemic has claimed millions of lives worldwide. In this report, we used a preclinical mouse model to investigate the prophylactic and therapeutic value of intranasal IFN-λ for this acute respiratory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Paralleling the potential, IFN-λ 1/3 has also been induced in early phases of infection and in convalescent COVID-19 patients ( 227 ). The results indicated that IFN-β and IFN-λ1 could block virus infection and inhibit the production of SARS-CoV-2 ( 226 , 228 ). In addition, the dysregulated production of type I IFNs and the exacerbated release of proinflammatory cytokines makes COVID-19 more severe ( 226 , 229 ).…”
Section: Cytokine Secretion Induced By Sars-cov-2 Infectionmentioning
confidence: 99%
“…Paralleling the potential, IFN-λ 1/3 has also been induced in early phases of infection and in convalescent COVID-19 patients ( 227 ). The results indicated that IFN-β and IFN-λ1 could block virus infection and inhibit the production of SARS-CoV-2 ( 226 , 228 ). In addition, the dysregulated production of type I IFNs and the exacerbated release of proinflammatory cytokines makes COVID-19 more severe ( 226 , 229 ).…”
Section: Cytokine Secretion Induced By Sars-cov-2 Infectionmentioning
confidence: 99%
“…In contrast, IFN-III has been shown to limit viral activities at the local level without being associated with inflammation [118][119][120], conversely restricting the neutrophil inflammatory functions then limiting tissue damage [120][121][122]. In the context of SARS-CoV-2 infection, in vitro and in vivo studies have demonstrated antiviral IFN-III activities in epithelial cells without excessive inflammation [89,91,92,123,124]. Furthermore, the protein expression of IFN-λ2/λ3 were reduced in nasopharyngeal swab samples from COVID-19-positive individuals [125].…”
Section: Ifn-λmentioning
confidence: 99%
“…Thus, while IFN-l expression appears to correlate inversely with COVID-19 severity, its mechanism(s) of protection is not well understood. Although IFN-l has been studied in animals in the context of SARS-CoV-2 infection (Boudewijns et al, 2020;Broggi et al, 2020a;Dinnon et al, 2020;Sohn et al, 2021) and has been postulated to have a protective antiviral role, the responding cell types and targets of action have not been identified.…”
Section: Introductionmentioning
confidence: 99%